2004
DOI: 10.1016/j.bbrc.2004.08.237
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization with vascular endothelial growth factor receptor-2 (VEGFR-2) is necessary for VEGFR-3 activity

Abstract: VEGFR-3 is essential for vascular development and maintenance of lymphatic vessel's integrity. Little is known about its cooperative effect with other receptors of the same family. Contrary to VEGFR-2, stimulation of VEGFR-3 by VEGF-C and -D failed to enhance its phosphorylation either in HEK293T or in PAE cells. These ligands were unable to induce angiogenesis of PAEC expressing VEGFR-3 alone. In the presence of VEGFR-2, VEGF-C and -D induced heterodimerization of VEGFR-3 with VEGFR-2. This heterodimerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 27 publications
3
41
0
1
Order By: Relevance
“…This suggests that additional ligands exist or that ligand-independent signaling occurs. Indeed, whereas VEGFA binds only to VEGFR-2, we and others have shown that VEGFA may induce formation of VEGFR-2/-3 heterodimers (13,14). This suggests that when cells express both receptors, VEGFR-3 inhibitors may also block some VEGFA signaling.…”
Section: Introductionmentioning
confidence: 75%
“…This suggests that additional ligands exist or that ligand-independent signaling occurs. Indeed, whereas VEGFA binds only to VEGFR-2, we and others have shown that VEGFA may induce formation of VEGFR-2/-3 heterodimers (13,14). This suggests that when cells express both receptors, VEGFR-3 inhibitors may also block some VEGFA signaling.…”
Section: Introductionmentioning
confidence: 75%
“…VEGFR also form homo-and heterodimers, which drives a complex series of signaling events leading to activation of many common growth factor signaling pathways (1). VEGFR-1 for example can synergize with VEGFR-2 and facilitate full activation of VEGFR-2 signaling (32,33), and VEGFR-3 also forms a heterodimer (34). Formation of these heterodimers would be prevented by an inhibitor of VEGFR-2 dimerization.…”
Section: Numbmentioning
confidence: 99%
“…14,37,38 However, it has been demonstrated that VEGFR-3 activity requires heterodimerization with VEGFR-2, which is also expressed on lymphatic vessels. [39][40][41] In this study, we have investigated the ability of NRP2 to interact with VEGFR-2 and VEGFR-3 and analyzed the consequences of such interactions on human endothelial cell survival and migration.…”
Section: Introductionmentioning
confidence: 99%